2015
DOI: 10.1071/an14540
|View full text |Cite
|
Sign up to set email alerts
|

Continuous bite monitoring: a method to assess the foraging dynamics of herbivores in natural grazing conditions

Abstract: Accurate estimates of bite mass and variations in the short-term intake rate of grazing herbivores has been historically considered as a fundamental methodological difficulty, a difficulty that increases with the complexity of the feeding environment. Improving these methodologies will help understand foraging behaviours in natural grazing conditions, where habitat structure and interactions among different forages influence feeding decisions and patterns. During the past 30 years, we have been developing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 72 publications
0
31
0
8
Order By: Relevance
“…Animals may have selected areas for grazing that departed significantly from the average for the inter-tussock stratum. Novel results by Bonnet et al (2015) confirmed that heifers take a significant proportion of bites from tussocks (~30% of bites), and these proportions show variation over time. The assumption of non-selective grazing exclusively within the inter-tussock is not a failure of our main hypothesis, but of our original conceptual model used to test the hypothesis.…”
Section: Bm Variationmentioning
confidence: 78%
“…Animals may have selected areas for grazing that departed significantly from the average for the inter-tussock stratum. Novel results by Bonnet et al (2015) confirmed that heifers take a significant proportion of bites from tussocks (~30% of bites), and these proportions show variation over time. The assumption of non-selective grazing exclusively within the inter-tussock is not a failure of our main hypothesis, but of our original conceptual model used to test the hypothesis.…”
Section: Bm Variationmentioning
confidence: 78%
“…The animal familiarization procedure aims to accustom the flock to the permanent presence of an unfamiliar person. This mutual familiarization procedure was detailed by Bonnet et al and Meuret and Provenza [25,26]. The observer is considered fully familiarized with the animal if he can get as close as 0.5 to 1.5 m, providing that it does not hamper the spontaneous movements of the goats [27][28][29].…”
Section: Familiarization Proceduresmentioning
confidence: 99%
“…Si, además, los tallos de las diversas plantas arbóreas forrajeras poseen elevados contenidos de fibra responsable de su rigidez (Valenciaga & Chongo, 2004) e inversamente ligada al consumo de alimentos (Forbes, 2000;Karsli & Russell, 2002) y también, según Laca, Shipley y Reid (2001) e Ingram et al (2013), existen muchas interacciones entre otros elementos morfológicos de las plantas, que se denominan "características anticalidad", así como del animal, del manejo de ambos y de las condiciones ambientales, entonces, determinar cuánto es consumido de una planta arbórea por los animales en el pastoreo es un procedimiento imprescindible y complejo (Bonnet et al, 2015), lo que sugiere la necesidad de investigaciones que generen tales informaciones para el manejo sostenible de la vegetación y que puedan ser aplicadas para adoptar estrategias de suplementación (González-Pech, Torres-Acosta & Sandoval-Castro, 2014). Se sabe, además, que los rumiantes pueden aprender de experiencias acumuladas para seleccionar los forrajes que consumen (Fisher, 2002).…”
Section: Introductionunclassified